PENERAPAN PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION (GI) UNTUK MENINGKATKAN HASILBELAJAR POKOK BAHASAN TEOREMA PHYTAGORAS PADA SISWA KELAS VIIID SEMESTER GANJIL SMPN 1 PAKUSARI TAHUN AJARAN 2012/2013 - Prihartanto, Y. Danni; Trapsilasiwi, Dinawati; Setiawan, Toto' Bara (Department of Mathematics Education , University of Jember, 2013)
Abstract.Group Investigationis one of thecooperative learning modelthat helpstudents to solvemathematics problemsin groups.The learning purposesof this researchare, (1)How dothe application ofcooperative learning modelGroup Investigationtype, (2) How dostudent activityby usingcooperative learning modeltypeGroup Investigation, (3)How do the student learningachievement student after join cooperative model Group Investigation type.This research usedtwolearningcycle. where thelearning result of first cycle88.57% andfor the second cycle is 94.29% forthe secondcycle. It can be concluded that the cooperative learning of Group Investigation type can be improve students achievement. Key Words : InvestigationGroup, Cooperative Learning, Mastery Learning.